Latihan Relaksasi Napas Dalam Pada Pasien TB Paru Untuk Meningkatkan Jalan Napas Di RSU Sembiring Deli Tua Tahun 2023 - Meta Rosaulina; Rini Silalahi; Reisy Tane; Joko Sutejo; Maria Puji Astuti (Jurnal Pengabdian Masyarakat Putri Hijau, 2023)
Tuberculosis is an abbreviation for TB, which is a disease caused by Mycobacteria tuberculosis which attacks the lungs and can infect other people through small particles released when sneezing or coughing. Symptoms may include a productive cough lasting 21 days, fever, shortness of breath, chest pain accompanied by coughing up blood, weight loss, and no appetite for inefficient airway clearance in tuberculosis patients caused by an ineffective cough. This will cause blockages over time. If not treated immediately, problems with clearing the airway will result in continuous coughing, shortness of breath, and secretions that accumulate in the respiratory tract. One treatment to clear the airways is to use deep breathing relaxation therapy. Deep breathing relaxation therapy involves breathing into the abdomen at a slow, rhythmic, and comfortable pace while closing your eyes while inhaling. The effect of this therapy is to divert or divert attention.